A simple and straightforward expression for curling probe electron density diagnosis in reactive plasmas. (20th March 2017) - Arshadi, Ali; Brinkmann, Ralf Peter; Hotta, Masaya; Nakamura, Keiji
Abstract: Active plasma resonance spectroscopy (APRS) refers to the family of plasma diagnostic methods which utilize the ability of plasmas to resonate at frequencies close to the plasma frequency. APRS operates by exciting the plasma with a weak RF signal by means of a small electric probe. The response of the plasma is recorded by a network analyzer (NA). A mathematical model is applied to derive characteristics like the electron density and the electron temperature. The curling probe is a promising realization of APRS. The curling probe is well-qualified for the local measurement of the electron density in reactive plasmas. This spiral probe resonates in plasma at a larger density dependent frequency than the plasma frequency. This manuscript represents a simple and straightforward expression relating this resonance frequency to the electron density of the plasma. A good agreement is observed between the proposed expression and the results obtained from previous studies and numerical simulations.